Annelida Polychaeta I. Fauna Iberica. Ramos, M.A. et al (Eds.) - Vieitez, J.M.; M.A.; Alós, C.; Parapar, J.; Besteiro, C.; Moreira, J.; Nunez, J.; Laborda, J.; San Martin, G. (2004)
Polychaeta I updates our current knowledge of the Polychaete Annelids from the coasts of the Iberian Peninsula and the Balearic Islands, through a description of the general morphological characters and most relevant aspects of the biology of the species of this taxonomic group. As a group that, to date, numbers almost a thousand species in our coasts, we did not consider it opportune to include a detailed account of all said species, however we do include identification keys of the different families as this is the most important taxonomic category to understand the great morphological variability that exists among this group of segmented marine worms. This volume also contains a detailed taxonomic review and an in-depth bibliography of the families Phyllodocidae, Hesionidae, Pilargidae, Nereididae, Nephtyidae, Paralacidoniidae, Chrysopetalidae y Pisonidae, in addition to keys of the different taxons to the species level. For each of the 129 cited species belonging to the above-mentioned families, we offer a detailed description of the species, accompanied by the corresponding iconography that highlights its most important anatomical characteristics, aspects of its biology, and its geographic distribution.
World Polychaeta Database (WPolyDb). Recommended citation is as Vieitez et al. The text is continuous, not in authored chapters